2016
DOI: 10.1080/19440049.2016.1267876
|View full text |Cite
|
Sign up to set email alerts
|

Single-laboratory validation of an LC-MS/MS method for determining florfenicol (FF) and florfenicol amine (FFA) residues in chicken feathers and application to a residue-depletion study

Abstract: A suitable analytical method is required to study the behaviour of florfenicol (FF) and its metabolite florfenicol amine (FFA) in broiler's feathers. An LC-MS/MS method was developed, assessed and intra-laboratory-validated for FF and FFA analyses. We chose cloramphenicol-d as an internal standard, acetone as a solvent for the extraction of the analytes and dichloromethane for the clean-up. Through LC-MS/MS analysis, we established a detection limit of 20 μg kg, as well as calculated quantification limits of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The results in this study agree with previous works and are particularly similar to those observed by Cornejo et al [ 30 ], as the concentrations of FF and FFA persisted for a longer period of time in chicken claws than the withdrawal time currently established in muscle tissues for the commercial formulation. Furthermore, for each sampling point, residue concentrations of these analytes were detectable at greater concentrations in claws than in samples of muscle and liver tissues that were sourced from the same animals.…”
Section: Discussionsupporting
confidence: 93%
“…The results in this study agree with previous works and are particularly similar to those observed by Cornejo et al [ 30 ], as the concentrations of FF and FFA persisted for a longer period of time in chicken claws than the withdrawal time currently established in muscle tissues for the commercial formulation. Furthermore, for each sampling point, residue concentrations of these analytes were detectable at greater concentrations in claws than in samples of muscle and liver tissues that were sourced from the same animals.…”
Section: Discussionsupporting
confidence: 93%
“…In another study by Cornejo et al [ 25 ], they determined that residues of florfenicol and florfenicol amine also remained in feathers for longer periods than the withdrawal time that has been established for muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of muscle and liver samples, the first step to process them was the removal of fats and grinding. Meanwhile, feather samples were first treated cryogenically with liquid nitrogen, as different studies have reported that this procedure improves grinding efficiency of feathers [ 23 , 25 , 26 ]. Then, samples were ground in an industrial Robot Coupe ® R4 table-top cutter food processor (Burgundy, France) to ensure their homogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…There is a need for methods that are able to detect the use of antibiotics administered over the entire life span of an animal, including treatments administered during the first days of the animals’ lives. In previous research focusing on the excretion of oxytetracycline [ 7 ], multiple fluoroquinolones (enrofloxacin, its metabolite ciprofloxacin [ 8 ], and flumequin [ 9 ]) and florfenicol and its metabolite florfenicol amine [ 10 ] to feathers, it has already been shown that antibiotic residues can still be detected in feathers long after treatment. In another study, different antibiotics in feather meal, originating from different countries, were detected, including antibiotics that are registered as banned substances in the country of origin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%